1-(3′,6′-Dihydroxy-3-oxo-3H-spiro[isobenzofuran-1,9′-xanthen]-5-yl)-3-[4-({4-[1-(4-fluorophenyl)-1H-imidazol-5-yl]pyridin-2-yl}amino)phenyl]thiourea methanol monosolvate - Francesco Ansideri; Dieter Schollmeyer; Pierre Koch (IUCrData, 2016)
The title compound, which crystallized as a methanol monosolvate, C41H27FN6O5S·CH3OH, was synthesized as a probe for a fluorescence polarization-based competition binding assay. The isobenzofuran fused-ring system is close to planar and orientated almost perpendicular to the central ring of the xanthene system. The dihedral angle between the benzene rings of the xanthene system is 10.0 (2)°, indicating a butterfly-like orientation. A short intramolecular C—F...π contact [F...π = 3.100 (4) Å and C—F...π = 139.9 (3)°] to the six-membered ring of the isobenzofuran system may influence the molecular conformation. The methanol solvent molecule is disordered over two orientations in a 0.6:0.4 ratio. In the crystal, the components are linked by numerous hydrogen bonds, generating a three-dimensional network.